Analisis Kontribusi Literasi Bahasa Indonesia terhadap Representasi dan Resolusi Matematis Mahasiswa FSB Universitas Negeri Gorontalo - Bagas H. Halim; Ria Eliyanti; Sri Diyanti H. Umar; Nur Fitriyani; Erinda Hakai; Annanda Dalanggo; Moh. Rafli N. Lajali; Naysillah Cahyani; Sri Rahmawati Lie; Meilina Widya Dali (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine the relationship between Indonesian language literacy and mathematical literacy, as well as to analyze the role of Indonesian language literacy in describing and solving mathematical word problems among students of the Faculty of Letters and Culture (FSB) at Universitas Negeri Gorontalo. Utilizing a quantitative approach with a descriptive-associative method, data were collected through a series of mathematical word problem tests based on linear equation systems administered to a sample of 22 active students. The sample was divided by department: 9 students from the English Department and 13 students from the Indonesian Department. The results showed that the students' level of information comprehension was classified as good (72%), supported by their language backgrounds. However, the ability to represent equations decreased to 61%, and the ability to solve mathematical calculations fell even further into the fair/poor category (54% fair; 46% poor) due to difficulties in determining procedural steps and calculation errors. The conclusion of this study indicates a gap between verbal comprehension and mathematical representation and resolution. While Indonesian language literacy is proven to play a crucial role in understanding the problems, it is not yet fully balanced with optimal analytical skills for resolution strategies. Therefore, integrated learning efforts are required to strengthen students' mathematical concepts and critical thinking skills.